ANALISIS PENURUNAN AKUNTABILITAS KINERJA MELALUI SISTEM AKUNTABILITAS KINERJA INTANSI PEMERINTAH (SAKIP) (Studi Kasus pada Dinas Perhubungan Kota Pekanbaru) - Ayi, Nasrun Kinanti D; Restu, Agust; Azhari, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims at the factors that influence the Performance Accountability of Government Agencies at the Transportation Service of Pekanbaru City experiencing a decrease in the assessment of the Performance Accountability Evaluation of Government Agencies through the Government Agencies Performance Accountability System. The population of this study were all employees of the Pekanbaru City Transportation Department which consisted of 197 employees. The sample in this study consisted of 7 people. The method of determining the sample is done by purposive sampling with certain criteria, namely for officials who work in the formulation unit of the Performance Accountability System of Government Agencies (Finance Section, Program Division, SAKIP Preparation Team, Head of Staff and General Secretary). The data used are primary data and data. Secondary. Data were collected using the direct interview method and supported by secondary data from the results of the Performance Accountability Evaluation of Government Agencies from the Inspectorate of Pekanbaru City. The data analysis technique used is descriptive analysis technique by describing the results obtained systematically. The results of this study, it was found that the factors that influence the performance of government agencies are found in the 5 components of the preparation of SAKIP. Performance planning 54.8% (30%), performance measurement 37.5% (25%), performance reporting 2.25% (15%) internal evaluation 1.29% (10) and target achievement 0% (20%). Improvement steps starting from the preparation of performance agreements, reporting to reviews on the Performance Accountability System of Government Agencies in the Transportation Office of Pekanbaru City.Keywords: Performance Accountability, Performance, Government Intasni Performance Accountability System, Government Agency Performance Accountability, Qualitative.